An exploration of physiotherapists' experiences of robotic therapy in upper limb rehabilitation within a stroke rehabilitation centre. (3rd April 2018) - Stephenson, Andrew; Stephens, John
Abstract: Purpose: Strokes are the world's leading cause of adult disability, with movement impairment being more common in the upper limb (UL). Robotic therapy (RT) is identified as an effective adjunct to promote movement but with limited effect on functional capabilities. There is currently limited research in user experience of RT, specifically that of physiotherapists. This study sought to explore physiotherapists' experience of using RT in rehabilitation of the UL, within a stroke rehabilitation centre in the north of England. Method: Physiotherapists ( n  = 6) shared their experiences of working with the InMotion2 robot through semi-structured interviews. Thematic analysis was employed to interpret data, identify emergent themes and interdependent relationships between them. Findings: Five interdependent themes were identified focused around individualized care, influenced by evidence for practice, human relationships, skill mix, and resources and resource management. All physiotherapists valued the use of RT as an adjunct to conventional therapy, although barriers to successful implementation seemed to dominate the views of some. Conclusions: RT was perceived positively by physiotherapists, regarded as an adjunct to conventional therapy. A framework to summarize the relationships of participants' views and experiences is proposed in an attempt to understand the influences on the clinical use of RT. Implications for Rehabilitation: Robotic therapy (RT) is valued as an adjunct to (conventional) person-centred rehabilitation. Resource management and skill mix are viewed as two key challenges to the successful implementation of RT. The production of evidence-based guidelines would be a useful development in the advancement.